USE OF ENGLISH TERMINOLOGY IN TECHNICAL UNIVERSITIES (American Journal of Interdisciplinary Research and Development, 2023)
This article aims to investigate the use of English terminology in the context of technical universities, where English has become a dominant language of technical communication. The research is based on a case study conducted at a prominent European technical university, and it addresses the challenges and opportunities that the use of English terminology poses for different stakeholders, including students, faculty, and industry partners. The findings suggest that while the use of English terminology can facilitate collaboration and enhance the internationalization of technical education, it can also create barriers for students and faculty who are not proficient in English and may lead to a loss of linguistic diversity in technical fields.